2020
DOI: 10.4314/ijbcs.v14i4.20
|View full text |Cite
|
Sign up to set email alerts
|

Effet des coûts de transaction sur la performance économique et l’adoption du coton biologique au Centre et Nord du Bénin

Abstract: Face au défi de la dégradation de l’environnement et des problèmes sanitaires liés à la production du coton conventionnel au Bénin, la production du coton biologique initiée depuis quelques décennies peine à se développer. Cet article s’intéresse à l’analyse de l’effet des coûts de transaction (CT) sur la performance économique et l’adoption du coton biologique au Centre et au Nord du Bénin. Basée sur un échantillon aléatoire de 408 producteurs dont 168 adoptants du coton biologique, l’étude a utilisé l’approc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 14 publications
1
1
0
3
Order By: Relevance
“…Also, women are particularly concerned about the harmful effects of chemical substances used in conventional production on the environment and on human health(Bassett 2017) and are therefore more favorable to the fair-trade organic production of cashew. This result corroborates with that ofAgalati and Degla (2020), Sodjinou et al (2015), Hougni and Kpadé (2012), Glin et al (2012) and Tovignan and Nuppenau, (2005) who all showed that women are more favorable to organic production than men. This is counter to Adekambi et al (2010) and Kpadenou et al (…”
supporting
confidence: 89%
See 1 more Smart Citation
“…Also, women are particularly concerned about the harmful effects of chemical substances used in conventional production on the environment and on human health(Bassett 2017) and are therefore more favorable to the fair-trade organic production of cashew. This result corroborates with that ofAgalati and Degla (2020), Sodjinou et al (2015), Hougni and Kpadé (2012), Glin et al (2012) and Tovignan and Nuppenau, (2005) who all showed that women are more favorable to organic production than men. This is counter to Adekambi et al (2010) and Kpadenou et al (…”
supporting
confidence: 89%
“…often more interested in organic production because it frees them from dependence on their husband (Agalati and Degla 2020;and Sodjinou et al 2015).…”
Section: Study Area Sampling and Data Collectionmentioning
confidence: 99%
“…Cette performance varie selon la nature (technique, économique, écologique, socio-territoriale etc.) ou le système de production étudié dans le secteur agricole ( Yabi et al, 2012;Yabi et al, 2016;Degla, 2020;Agalati et al, 2022;) ou encore selon les filières d'activité de ces exploitations (Mensah et al, 2011;Degla, 2012;Tovignan et al, 2018;).…”
Section: Discussionunclassified
“…Tout comme les entreprises agricoles détenues par les jeunes dans la zone d'étude, Ayedegue (2020) a trouvé une durabilité économique moyenne au niveau des exploitations maraichères au Nord Est du Bénin. Selon Agalati et al (2022), les exploitations de coton du Nord et du centre Bénin, sont dans l'ensemble économiquement rentables en considérant la marge nette. Pour sa part Tovignan et al (2018) révèlent que 49% des exploitations cunicoles à Parakou au Nord du Bénin sont rentables économiquement.…”
Section: Discussionunclassified
See 1 more Smart Citation